2010
DOI: 10.1086/652525
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characteristics of Staphylococcus aureus Colonization among Healthcare Professionals in an Urban Teaching Hospital

Abstract: The observed prevalence of S. aureus and MRSA colonization among HCPs exceeds previously reported prevalences in the general population. The proportion of community-associated MRSA among all MRSA in this colonized HCP cohort reflects the distribution of the USA300 community-associated strain observed increasingly among US hospitalized patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
56
3
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 31 publications
9
56
3
3
Order By: Relevance
“…38 This study's overall prevalence of S. aureus (24.3%) and MRSA (0.99%) is also similar to those noted for the U.S. population and published by Kuehnert et al, 28 who reported S. aureus and MRSA colonization prevalence estimates as 32.4% (95% CI, 30.7-34.1) and 0.8% (95% CI, 0.4-1.4), respectively. However, our study showed a lower prevalence rate (25.5% for S. aureus and 0% for MRSA) among HCE workers than previous studies, such as Elie-Turenne et al 39 who reported a 43.8% prevalence for S. aureus and a 15.2% prevalence for MRSA in healthcare professionals, and Barbosa et al 40 who reported a 5% MRSA prevalence in house staff in their study, all from surgical rather than medical house officers. In addition, Halablab et al 41 reported contact with healthcare workers as a risk factor for nasal colonization.…”
Section: Discussioncontrasting
confidence: 79%
“…38 This study's overall prevalence of S. aureus (24.3%) and MRSA (0.99%) is also similar to those noted for the U.S. population and published by Kuehnert et al, 28 who reported S. aureus and MRSA colonization prevalence estimates as 32.4% (95% CI, 30.7-34.1) and 0.8% (95% CI, 0.4-1.4), respectively. However, our study showed a lower prevalence rate (25.5% for S. aureus and 0% for MRSA) among HCE workers than previous studies, such as Elie-Turenne et al 39 who reported a 43.8% prevalence for S. aureus and a 15.2% prevalence for MRSA in healthcare professionals, and Barbosa et al 40 who reported a 5% MRSA prevalence in house staff in their study, all from surgical rather than medical house officers. In addition, Halablab et al 41 reported contact with healthcare workers as a risk factor for nasal colonization.…”
Section: Discussioncontrasting
confidence: 79%
“…Increased rates of MRSA colonization among HCWs have at least 3 important implications. First, HCWs may become infected by their own MRSA carriage strains; second, they could serve as a route of cross-transmission to patients; and finally, they may introduce the pathogen into their communities [12]. Several studies in Arabic countries and worldwide have reported that the rate of the nasal carriage of S. aureus and MRSA among HCWs ranges from 10.1%-76% [10,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…More recent data are in agreement with this, and it is widely believed that nasal colonisation provides a natural reservoir that facilitates ongoing habitation and propagation of S. aureus in human populations. (Elie-Turenne et al, 2010;Mermel et al, 2010). Nasal application of mupirocin has been proven to eradicate nasal carriage of S.aureus in up to 98.5% of cases (Taal et al, 2006).…”
Section: Nasal Eradication Of S Aureusmentioning
confidence: 99%